CT patterns in histopathologically complex cavernous hemangiomas. - Ahmadi, J; Miller, C A; Segall, H D; Park, S H; Zee, C S; Becker, R L (American Journal of Neuroradiology, 1985)
Computed tomographic (CT) studies were correlated with microscopic findings in 10 histologically verified cavernous hemangiomas in nine patients. In four of the 10 lesions, two or more distinct types of cerebrovascular malformations were identified histopathologically. These included arteriovenous malformations, venous malformations, and telangiectasis. Such coexistence of various types of cerebrovascular malformations has been reported rarely. In each of the four combined lesions, there was evidence of recent or old hemorrhage. The CT findings were nonspecific and were similar to those seen in a variety of intracranial pathologic conditions.